Development of a Board Game Media in Islamic Religious Education to Enhance Student Learning Motivation - Hadiyanto, Anniza Wiwied Rahayu; Perawironegoro, Djamaluddin (Journal of Indonesian Progressive Education, 2025)
The aims of this study is to develop a board game as an educational tool for Islamic Religious Education and to evaluate its effectiveness in enhancing students' learning motivation. The method in this study uses development research with the R&D with a qualitative and quantitative approach. The results of this study are development products in the form of Board Game learning media showing that the development of learning media is considered feasible by learning media experts with minor revisions obtaining 78% then by researchers made revisions and became 84%. While the assessment of the material expert with a percentage of 93% with the category is very feasible. Then based on SPSS 29 statistical calculations, it was found descriptively that there was a difference in the results of filling out the learning motivation instrument before using the Board Game learning media compared to after using the product with a sig result of 0.01 which means that the use of Board Game learning media has a significant difference in increasing student learning motivation. So that from the assessment that has been explained, it can be concluded that the Board Game developed is good for use in learning, especially Islamic Religious Education class X subjects at SMAIT Samawa Cendekia.